EFEKTIVITAS PEMBERIAN INFRARED, ELECTRICAL STIMULATION, FACIAL EXERCSIE PADA KASUS BELL’S PALSY: CASE REPORT - Ardian Rifcky Muhammad; Wijianto Wijianto; Eko Prihati (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Introduction : Bell's palsy is a facial nerve dysfunction that affects the muscles of facial expression. Weakness of the facial muscles on one side greatly affects people with Bell's palsy, the subject complains of difficulty in facial expression, difficulty in activities involving oral, difficulty speaking, visual disturbances (dry eyes). , and there is pain behind the ear. In this case, Bell's palsy patients experience problems in their productivity in communicating and socially also decreasing because the patient's confidence decreases due to an asymmetrical face. The modalities that will be used to treat cases of Bell's palsy include Infrared (IR), ES (electrical stimulation), and facial exercises (FE). Objective: to prove the effectiveness of administering IR, ES, and FE on the motor control ability of Bell's palsy patients. Methods: Single subject research conducted on an 18 year old teenager with Bell's palsy. Results: The evaluation was carried out using the Facial Muscle Testing Manual and the Ugo Fisch Scale. Conclusion: There was an increase in function in the form of muscle strength and functional facial in Bell's palsy patients after being given IR, ES, and FE for 4 weeks.Keyword : Bell’s palsy, infrared, electrical stimulation, facial exercise